GPU-accelerated ray-casting for 3D fiber orientation analysis - Shkarin R. Roman; Shkarina S. N. Svetlana Nikolaevna; Weinhardt V. Venera; Surmenev R. A. Roman Anatolievich; Surmeneva M. A. Maria Alexandrovna; Shkarin A. Andrei; Mikut R. Ralf (2020, 2020)
Title screen